2022
DOI: 10.3390/ani12131715
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Blend of Essential Oils Plus 25-Hydroxy-Vit-D3 Versus Monensin Plus Virginiamycin Combination in Finishing Feedlot Cattle: Growth Performance, Dietary Energetics, and Carcass Traits

Abstract: Ninety crossbreed bulls (349.5 ± 8.25 kg initial weight) were used in an 87day trial to compare the effects of a blend of essential oils plus 25-hydroxy-Vit-D3 (EO + HyD) versus the combination of monensin with virginiamycin (MON + VM) on feedlot growth performance and carcass characteristics. Dietary treatments (nine replicates/treatment) were supplemented with 40 mg/kg diet dry matter of MON + VM (equal parts) or with 120.12 mg/kg diet dry matter of a combination of standardized mixture of essential oils (12… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
(82 reference statements)
1
3
0
Order By: Relevance
“…Very little has been reported regarding the influence of the combination of essential oils plus vitamin D3 (EOD3) on DM intake in ruminants. In the feedlot cattle, EOD3 supplementation did not affect DM intake when supplemented under HAHL or under favorable climatic conditions [13,48,49]. Consistent with the present study, Escobedo-Gallegos et al [14] observed that, under HAHL conditions, EOD3 (0.12 mg/kg) did not affect DM intake of finishing lambs.…”
Section: Discussionsupporting
confidence: 86%
See 1 more Smart Citation
“…Very little has been reported regarding the influence of the combination of essential oils plus vitamin D3 (EOD3) on DM intake in ruminants. In the feedlot cattle, EOD3 supplementation did not affect DM intake when supplemented under HAHL or under favorable climatic conditions [13,48,49]. Consistent with the present study, Escobedo-Gallegos et al [14] observed that, under HAHL conditions, EOD3 (0.12 mg/kg) did not affect DM intake of finishing lambs.…”
Section: Discussionsupporting
confidence: 86%
“…However, in the present study there were no appreciable effects of D3 in combination with EO on carcass measures. In feedlot cattle fed a corn-based finishing diet (2.14 Mcal NE m /kg diet), supplementation with EOD3 (120 mg EO+0.12 mgD3/kg diet) increased LM area, but did not affect other carcass measures [49]. In Holstein steers fed a steam flaked corn-based diet (2.20 Mcal NE m /kg) during a 285 d growing-finishing period, supplementation with EOD3 (200 mg/kg diet) reduced carcass fat thickness without effects on other carcass characteristics [48].…”
Section: Discussionmentioning
confidence: 99%
“…Because of the wide diversity of form and composition of EO, their effects on DMI likewise vary [40]. In this sense, compared to non-supplemented treatments, the blend of essential oils (thymol, eugenol, vanillin, guaiac, and limonene) used alone or in the combination EO + D3 showed a similar DMI in previous studies when supplemented in feedlot cattle [41][42][43] and in lambs [13,44]. Similarly, a blend of carvacrol and cynamaldehyde or cynamaldehyde alone failed to increase DMI when supplemented in lambs at levels of up to 400 mg/kg diet DM [45,46] or in lactating cows [47].…”
Section: Discussionmentioning
confidence: 71%
“…This concern has led livestock industries to look for possible alternatives, among which are, natural additives such as probiotics and essential oils [ 7 ]. Probiotics and essential oils alter rumen fermentation and promote gastrointestinal (GIT) health; in addition, some antioxidant and immunological effects have been attributed; all these effects aid several beneficial responses primarily on growth rate and/or feed efficiency in lambs [ 8 , 9 , 10 , 11 ]. Therefore, probiotics and essential oils favor changes in ruminal microorganisms and gastrointestinal health analogous to antibiotics [ 12 ].…”
Section: Introductionmentioning
confidence: 99%